The Effect of Intra-Organizational Factors on Human Resource Development in the Implementation of Knowledge Management Components in Small Knowledge-based Companies - Aidi, Mohammad; Fazelpur, Fatemeh; Heydarnezhad, Zahra; Behzadi, Arghavan (Archives of Business Research, 2021)
The present study aims to investigate the effect of intra-organizational factors on human resource development in small knowledge-based companies by considering the components of knowledge management in. The study adopts a practical approach and descriptive-correlation method. The data collection instrument is questionnaire. To measure intra-organizational factors the questionnaire of Fazili and Alishahi (2012), to measure knowledge management the questionnaire of Patrick et al.( 2009), and to human resources development a researcher-made questionnaire are used. The statistical population includes 450 managers and shareholders from knowledge-based companies in Lorestan Province, Iran. Based on Krejcie and Morgan (1985) table, a sample size of 208 people was selected using simple random sampling. Data were analyzed using SPSS and Lisrel. Findings highlight that intra-organizational factors have a positive and significant effect on human resource development and knowledge management components as well as knowledge management components have a positive and significant effect on human resource development.